DIGITAL MONITORING OF RETURN-TO-PERFORMANCE AFTER ACHILLES TENDON RUPTURE IN BASKETBALL: A NARRATIVE REVIEW - Rosa, Katarzyna; Żurek, Paweł; Danielczyk, Daria; Babicz, Michał; Pałubska, Jagoda; Muller, Oliwer; Malatyńska, Natalia; Czyżewski, Wiktor; Słoma, Agata; Chudzicki, Kamil (International Journal of Innovative Technologies in Social Science, 2026)
Achilles tendon rupture (ATR) is among the most consequential injuries in basketball because it interrupts participation, alters explosive lower-limb function, and often prevents full recovery of preinjury competitive output. Recent studies in the National Basketball Association, Women’s National Basketball Association, and National Collegiate Athletic Association show that many athletes do return to competition after ATR, yet substantial losses in playing time, efficiency, durability, and career longevity remain common. At the same time, contemporary Achilles rehabilitation literature shows considerable variation in how readiness for return is judged, with many pathways still relying more on elapsed time than on multidimensional recovery data. This narrative review synthesizes recent PubMed-indexed evidence on basketball-specific ATR outcomes, ATR rehabilitation, and digital monitoring technologies relevant to return-to-performance. The review focuses on wearable sensors, portable strength devices, force-plate testing, ultrasound and magnetic resonance imaging, electronic patient-reported outcomes, markerless video, and artificial intelligence-assisted analytics. A staged basketball-specific framework is proposed in which digital tools are aligned with early protection, progressive loading, court reintroduction, and return-to-performance phases. The synthesis suggests that digital monitoring is most useful when it quantifies tendon status, plantar-flexor recovery, gait and jump asymmetry, external workload, repeated court exposure, and psychological readiness over time. Current evidence does not support fully automated clearance decisions, but it does support replacing calendar-based progression with a criteria-based, sport-specific, and digitally informed rehabilitation model.